2003
DOI: 10.1007/s00784-002-0193-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness of a novel "ceramic restorative cement" after treatment with different polishing techniques in vitro

Abstract: The aim of this study was to determine the surface roughness of a novel calcium aluminate cement (CAC) intended for posterior restorations after treatment with different polishing devices in vitro. Forty-eight CAC specimens were polished with diamond burs at 15,550 rpm or 27,000 rpm, Sof-Lex discs, Jiffy points, Shofu silicone points, and Aaba universal polisher. Amalgam specimens were polished with Shofu silicone points and used as reference. Roughness was measured using a profilometer. The smoothest CAC surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Sunnegardh et al observed a similar problem for calcium aluminate cement [131]. Its heterogeneous microstructure and surface porosity limited its polishability, compared to resin composite and polyacid-modified resin composite [132]. Higher porosity (80% as opposed to 58%) decreased mechanical properties of porous poly( l -lactide-co- d , l -lactide) scaffolds: compressive strength decreased from 11.0 to 2.7 MPa and modulus from 168.3 to 43.5 MPa [133].…”
Section: Porous Biomaterials In Orthopaedic and Dental Applicationsmentioning
confidence: 99%
“…Sunnegardh et al observed a similar problem for calcium aluminate cement [131]. Its heterogeneous microstructure and surface porosity limited its polishability, compared to resin composite and polyacid-modified resin composite [132]. Higher porosity (80% as opposed to 58%) decreased mechanical properties of porous poly( l -lactide-co- d , l -lactide) scaffolds: compressive strength decreased from 11.0 to 2.7 MPa and modulus from 168.3 to 43.5 MPa [133].…”
Section: Porous Biomaterials In Orthopaedic and Dental Applicationsmentioning
confidence: 99%
“…The combination of the quantitative and qualitative data can conduct to the obtaining of the tridimensional qualitative values of the tested surfaces [76][77][78].…”
Section: Resultsmentioning
confidence: 99%
“…Sunnegårdh-Grönberg et al also evaluated the physical properties of DD in a series of publications. [7][8][9] The aim of the first study was to compare a new ceramic restorative cement for posterior restorations, DD, with other types of tooth-colored materials for direct use as regards to hardness and in vitro wear. 7 Four hybrid resin composites (RCs)-one polyacid-modified RC, one resin-modified glass ionomer (RMGI) cement, one conventional glass ionomer cement (GIC), and one zinc phosphate cement, an experimental version as well as the marketed version of the ceramic restorative cement-were investigated.…”
Section: Use Of Calcium Aluminate As a Direct Dental Restorative Matementioning
confidence: 99%
“…Sunnegårdh‐Grönberg et al . also evaluated the physical properties of DD in a series of publications . The aim of the first study was to compare a new ceramic restorative cement for posterior restorations, DD, with other types of tooth‐colored materials for direct use as regards to hardness and in vitro wear .…”
Section: Use Of Calcium Aluminate As a Direct Dental Restorative Matementioning
confidence: 99%
See 1 more Smart Citation